Cobalt‐Catalyzed Asymmetric Alkylation of (Hetero)Arenes with Styrenes. Issue 26 (5th May 2022) - Qin, Tao; Lv, Guowei; Miao, Huanran; Guan, Meihui; Xu, Chunlu; Zhang, Ge; Xiong, Tao; Zhang, Qian
Abstract: An efficient and general intermolecular Cobalt(II)‐catalyzed asymmetric alkylation of styrenes with (hetero)arenes including indoles, thiophene and electron rich arenes has been developed, providing straightforward access to enantioenriched alkyl(hetero)arenes with high enantioselectivity. Mechanistic studies suggest that the reaction underwent a CoH‐mediated hydrogen atom transfer (HAT) with alkenes, followed by a pivotal catalyst‐controlled SN 2‐like pathway between in situ generated organocobalt(IV) species and aromatic nucleophiles. This is the first CoH‐catalyzed asymmetric hydrofunctionalization using carbon nucleophiles, providing a new strategy for asymmetric Friedel–Crafts type alkylation. Abstract : A highly efficient Co‐catalyzed enantioselective alkylation of alkenes with indoles, thiophenes and electron rich arenes has been developed. This is the first CoH‐catalyzed asymmetric hydrofunctionalization using carbon nucleophiles via hydrogen atom transfer.